Mini Factory Laboratory From Technology Reverse Engineering Ballet Reactors in Struvite Formation - L Edahwati; S Sutiyono; W D Lestari; R D Issafira; W Saputro; A K Faizin; N Adyono; T P Sari (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2021)
Reverse Engineering (RE) can be interpreted as procedures and processes in dismantling an object to find out the materials, working methods, or technology used so that the object can function properly. Design activities using the reverse engineering concept make it easier for students to understand product specifications, product advantages and disadvantages, product production processes and production cost estimates before designing new products. The laboratory is one place that can be used to carry out the reverse engineering process. The bulkhead reactor is an alternative to the stirred tank reactor with the aim that the resulting product is maximized both in terms of quantity and morphology or shape of the material. The benefit of disassembling this product is as a first step in understanding the concept of reverse engineering in the task of designing machines or tools. From the results of the study, it was found that the formation of struvite occurred at pH 9 using an air flow rate of 1 l/minute.